Dampak Ditetapkannya Peraturan Daerah Nomor 9 Tahun 2016 Tentang Pembentukan dan Susunan Perangkat Daerah Terhadap Kinerja Satuan Kerja Perangkat Daerah (SKPD) di Lingkungan Pemerintah Provinsi Jawa Tengah - Firdaus Nuzula Rizki (Universitas Negeri Semarang, 2019)
The purpose of this article is to examine the impact of enacting Perda No. 9 of 2016 on the performance of SKPD and budget differences before and after the SKPD downsizing. the method of approach used is Sociological Juridical. The results showed the impact of the enactment of Regional Regulation No. 9 of 2016 concerning the Formation and Arrangement of Regional Apparatuses on the Performance of Regional Work Units (SKPD) in the Central Java Provincial Government Environment is the change in the number of SKPDs which resulted in changes in the quantity number of staff, the organizational structure in each SKPD, then changes are also felt in the SKPD's performance due to the grading and most recently there is a change in the budget issued by the Central Java Provincial Government due to the SKPD downsizing. The conclusions of this study are: (1) The impact of the enactment of Regional Regulation No. 9 of 2016 concerning the Formation and Arrangement of Regional Apparatuses on the performance of SKPD in the Central Java Provincial Government is more optimal and effective because it is in accordance with the main tasks and functions as well as the appropriate workload, although there is a slight obstacle to the task adjustment at an early stage it is not an obstacle considering the professionalism of employees in the Central Java Provincial Government; (2) Comparison of the budget before and after the SKPD downsizing naturally occurs, the budget issued is higher in view of the addition of structural officials in each SKPD and the existence of Regency / City Regional Government which is the Central Java Provincial Government's affairs.